Specificities and challenges of the Mano River Union (UFM) in the dynamics of regional integration in West Africa (1959 to 2014) - (:unkn) unknown (My University, 2018)
After the accession of the West African countries to independence, several supranational alliances were sealed. But, the search for the Union was done in a certain ideological contrariety because, there were panafricanists and the researchers of the Regional Economic Communities among the heads of state. It is in this context that three integration organizations emerged: the Mano River Union (UFM), the Community of West African States (ECOWAS) and the Community of West African States (ECOWAS). States of West Africa (CEAO), later became WAEMU. The MRU was created on the basis of geographical proximity and taking into account the centuries-old socio-economic and cultural links between identical settlements. Its purpose was to facilitate commercial transactions between populations separated by the colonial frontier. But, the real problem was the question of markets. In the face of globalization, relatively small countries in terms of population have often struggled to integrate into the global economy. They organized themselves in pools of resources. However, from 1973 to 2014, the UFM failed to transform its member countries for two reasons: First, in its structure, instead of creating a regional commission, Member States set up a general secretariat. Secondly, because of the socio-political crises, the MRU member countries have made less concrete achievements.
Keywords: African Research